Situasi Tuberkulosis di Empat Kabupaten Kota di Pulau Sumatera dan Banten - Ajeng Tias Endarti; Izza Suraya; Muttaqien Muttaqien; Adelia Ulya Rachman; Rizki Tsalatshita Khair M (Faculty of Public Health, Hasanuddin University, Makassar, 2018)
Situational and costing analysis of TB burden in district level is rarely conducted eventhough its importancesin planning, budgeting, costing and evaluating TB care services. Study conducted in Tangerang District,Tanggamus District, Metro City and Dumai City with mixed method approach. Quantitative data collection usedsecondary data to current situation and cost of TB programme. Meanwhile qualitative data collection throughround table discussion with stakeholders. TB incidence and success rate of medication were highest in TanggamusDistrict. Metro City had the highest incidence and cure rate. The highest TB costing were allocated in TangerangDistrict, Rp. 6.737.303.630,-. Within all regions, costing washighly allocated for drug. Problems in TB controlwere unstandardized TB care, underestimated data, lack of case finding, limited man power for TB programme,lack of CSR contribution, lack of promotive and preventive activity, bad stigma, difficulty in monitoring and evaluationand cantack survey, and specific issues among low income and worker population. TB control among thesefour regions were not optimized, the we recommend to developing the policy in district level as an umbrella tostrengthen the budget and cross-sectoralcollaboration.